Enhancing Anti-Corruption Literacy and Strengthening the Strategic Role of Youth Organizations in Government Oversight in Serang City - Mahpudin Mahpudin; Rahmi Hidayati (Yayasan Keluarga Guru Mandiri, 2025)
This community services initiative aims to enhance anti-corruption literacy and strengthen the role of youth organizations in overseeing governance in Serang City. The program is motivated by the high incidence of corruption cases in the public sector and the low level of civic participation, particularly among young people, in monitoring government performance. The implementation method comprises three stages: preparation, execution, and evaluation. The outreach materials cover fundamental concepts of corruption, the role of youth in participatory oversight, regulations on public information transparency, and the utilization of digital reporting platforms such as Jaga.id. The activity involved 20 participants from UNTIRTA and UIN SMH Banten, all of whom are members of KAMMI Banten. Evaluation results indicate a significant improvement in participants' understanding, with the proportion of participants categorized as having